Root and Heart Rots in Acacia mangium Plantations in India - Mehrotra, M. D.; Pandey, P. C.; Chakrabarti, K.; Sharma, Suresh; Hazra, K. (Indian Forester, 1996)
Root-rot of Acacia mangium by Ganoderma lucidum and heart rots by Phellinus pachyphloeus and Trametes palustris have been recorded from plantations raised in West Bengal. The exotic appears to be highly susceptible to Ganoderma root-rot which is quite prevalent in Midnapore Forest Division. Heavy mortality in 1985 plantation is viewed with concern by the State Forest Department. Effective measures to keep the disease in check have been outlined. Heart rots caused by Phellinus pachyphloeus and Trametes palustris are the first records of decay in standing trees of A. mangium in India. Though decay, at present, is not a serious problem it is likely to be highly damaging in older stands in view of the progressive nature of decay. Preventive measures for heart rots are recommended.